Effect of Pre-Pregnancy BMI & Gestational Weight Gain on Fetomaternal Outcome - I. Saranya; G. Sindhujha Sekar; E. Vijayabharathi; R. Priyanka (The Bioscan, 2026)
This prospective observational cohort study assessed the effect of pre-pregnancy body mass index (BMI) and gestational weight gain (GWG) on feto-maternal outcomes among 300 antenatal women followed from the first trimester until delivery and one week postpartum. Nearly half of participants had normal BMI, while 18% were underweight and 34% were overweight or obese. Adequate GWG was observed in 52%, whereas 24% each had inadequate and excessive GWG. Increasing BMI was significantly associated with gestational hypertension, pre- eclampsia, gestational diabetes mellitus, caesarean delivery and postpartum complications. Inadequate GWG was associated with low birth weight, preterm birth and NICU admission, while excessive GWG was associated with hypertensive disorders, gestational diabetes, operative delivery and macrosomia. Multivariate analysis identified overweight, obesity, inadequate GWG and excessive GWG as independent predictors of composite adverse feto- maternal outcomes. Preconception BMI optimisation, trimester-wise weight monitoring and individualised antenatal nutritional counselling are essential to improve maternal and neonatal outcomes.